Health Literacy as a Social Determinant of Diabetes Outcomes: Implications for Equity and Population Health - Nada Hesham Elawady, Samy Mohamed Seleim, Marwa Bayomi Awadallah, Amany Rashad Aboel Seoud (Pegem Journal of Education and Instruction, 2024)
Background: Diabetes mellitus is a major global public health concern, driven not only by biological and behavioralfactors but also by social determinants that shape individuals’ capacity to prevent, manage, and live well with the disease.While advances in clinical care have improved diabetes treatment, persistent inequities in outcomes across socioeconomic, ethnic, and geographic groups indicate that biomedical approaches